A pilot study of self-determination, online media credibility and Noncommunicable Disease (NCDs) prevention behavior - Ramlan, Aini Faezah; Ridzuan, Abdul Rauf; Hassan, Mohd Sufiean; Ismail, Siti Nasarah (Faculty of Communication & Media Studies, 2025)
This pilot study aimed to investigate the reliability and validity of self-determination, online media credibility, and noncommunicable disease (NCD) preventative behavior among Malaysian public university students. A quantitative method was used, with an internet survey as the tool, and the questionnaire was created using existing research. This research focuses on a limited sample size (n = 52). A total of 52 people completed the survey, which included assessments of the independent variable, self-determination; the mediating variable, online media credibility; and the dependent variable, NCD preventative behavior. To confirm the instrument's quality, validity, reliability, and normality tests were performed through expert review and data analysis using SPSS software. The results showed that the instruments were dependable, and the data was regularly distributed. This exploratory research also found that university students had a favorable perception of self-determination, trust in online media, and engagement in NCD preventative behavior. According to these findings, the instruments are appropriate for use in the main study. However, more study with a bigger sample size is required to validate and reinforce these initial findings.